Factors of the labor area and its influence on the organizational climate on the workers of the Silver Lake S.A.C company of the city of Tacna, 2017 - Carrasco Uruchi, Tahnee Lizbeth (2019)
The main objective of this research is to measure the influence of the factors of the labor area in the organizational climate in the group of workers of Silver Lake S.A.C. The proposed model is evaluated based on measures present in a company in the city of Tacna and it is investigated which have the greatest impact on certain organizational outcome variables. The methodology of this research work corresponds to the type of basic research, and the design of the research is explanatory in order to establish the level of influence of the factors of work activity in the organizational climate of the company Silver Lake S.A.C. The obtained results allow to verify that the age, the masculine sex and the areas like the administration, control, and distribution are those that greater negative influence have on the organizational climate of the company.